Clearing of alang-alang steppe land in South Sumatera, Indonesia - Pramudya, Bambang; Singh, Gajendra; Olesen, Svend Elsnab; Koike, Masayuki; USAID-ASEAN (Bangkok : Asian Institute of Technology, 1981)
An experiment was carried out on alang-alang area in South Sumatera., Indonesia, to compare three methods which might be used in alang-alang land clearing. These were mechanical, a combination of mechanical-biological, and a mechanical- chemical method. Each method was tested with three level treatments, totalling nine treatment combinations. Observations were taken to determine field performance of land clearing machinery and rate of alang-alang regrowth up to three months after land clearing. Comparison among the given treatments was evaluated in the term of costs and the rate of alang-alang regrowth after land clearing, both in its density and overground biomass. The lowest regrowth rate was found in the clearing using a combination of mechanical-biological method, whereas the mechanical method exhibited the highest regrowth rate. The mechanical-chemical method entailed the highest cost, while the costs of the mechanical-biological method were slightly higher than the mechanical method.
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1981
Keywords: Clearing of land -- Indonesia -- Sumatera, South